Development of resistance to nymphs of Amblyomma cajennense ticks (Acari : Ixodidae) in dogs - Mukai, Luciana S. [UNESP]; Castro Netto, A. [UNESP]; Szabó, M. P J [UNESP]; Bechara, G. H. [UNESP] (New York Acad Sciences, 2002)
Ticks have long been regarded as constraints to humans and domestic animals, but hosts often develop resistance to ticks after repeated infestations. The purpose of this investigation was to study the possible acquisition of immunity in domestic dogs to nymphs of A. cajennense by determining the tick alimentary performance after successive controlled infestations. Mean engorged weight of nymphs was not significantly different among the three infestations; molting rate from nymph to adult ticks, and the percentage of nymph recovery were also very close in all infestations. These results are similar to those obtained in studies of the dog-adult Rhipicephalus sanguineus interface. It is concluded that domestic dogs do not develop resistance against nymphs of A. cajennense ticks.
Keywords: Amblyomma cajennense; Rickettsia rickettsii; Tick infestation; animal experiment; arthropod; conference paper; controlled study; dog; domestic animal; feeding; host resistance; immunity; infestation; molting; nonhuman; recurrent disease; tick; Animals; Arachnid Vectors; Dog Diseases; Dogs; Host-Parasite Relations; Immunity, Natural; Ixodidae; Molting; Nymph; Tick Infestations; Acari; Amblyomma; Animalia; Arachnida; Arthropoda; Canis familiaris; Canis lupus; Hexapoda; Rhipicephalus; Rhipicephalus sanguineus; Rickettsia